Yield of table beets (Beta vulgaris var, conditiva) after pre-sowing treatment of seeds by ozonation and freezing - Miroshnichenko, Tetiana; Bashtan, Natalia; Mozgovska, Hanna; Ivchenko, Tetiana; Kuts, Oleksandr; Kovalenko, Galyna; Shevchenko, Nadiia (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):303